Field guide to freshwater invertebrates of North America - Thorp, James H.; Rogers, D. Christopher (Burlington, MA : Academic Press, 2011)
"The Field Guide to Freshwater Invertebrates of North America focuses on freshwater invertebrates that can be identified using at most an inexpensive magnifying glass. This Guide will be useful for experienced nature enthusiasts, students doing aquatic field projects, and anglers looking for the best fish bait, lure, or fly. Color photographs and art, as well as the broad geographic coverage, set this guide apart. 362 color photographs and detailed descriptions aid in the identification of species -- Introductory chapters instruct the reader on how to use the book, different inland water habitats and basic ecological relationships of freshwater invertebrates -- Broad taxonomic coverage is more comprehensive than any guide currently available."--Publisher's description.
Part III. Ecology and Identification of Specific Taxa -- Chapter 5. Sponges: Phylum Porifera -- Chapter 6. Hydra and Jellyfish: Phylum Cnidaria -- Chapter 7. Flatworms: Phylum Platyhelminthes, Class Turbellaria -- Chapter 8. Hairworms: Phylum Nematomorpha -- Chapter 9. Snails: Phylum Mollusca, Class Gastropoda -- Chapter 10. Mussels and Clams: Phylum Mollusca, Class Bivalvia -- Chapter 11. Aquatic Segmented Worms and Leeches: Phylum Annelida -- Chapter 12. Moss Animals: Phylum Ectoprocta, or Bryozoa -- Chapter 13. Introduction to Freshwater Invertebrates in the Phylum Arthropoda -- Chapter 14. Mites and Spiders: Subphylum Chelicerata, Class Arachnida -- Chapter 15. Fairy Shrimp, Tadpole Shrimp, Clam Shrimp, and Water Fleas: Subphylum Crustacea, Class Branchiopoda -- Chapter 16. Copepods, Fish Lice, and Seed Shrimp: Subphylum Crustacea, Classes Maxillopoda and Ostracoda -- Chapter 17. Aquatic Sow Bugs, Scuds, and Opossum Shrimp: Subphylum Crustacea, Class Malacostraca, Superorder Peracarida -- Chapter 18. Crayfish, Crabs, and Shrimp: Subphylum Crustacea, Class Malacostraca, Order Decapoda -- Chapter 19. Introduction to Insects and their Near Relatives: Subphylum Hexapoda -- Chapter 20. Mayflies: Insect Order Ephemeroptera -- Chapter 21. Dragonflies and Damselflies: Insect Order Odonata -- Chapter 22. Stoneflies: Insect Order Plecoptera -- Chapter 23. True Bugs: Insect Order Hemiptera -- Chapter 24. Hellgrammites, Spongillaflies, Caterpillars, and Others: Minor Aquatic Insect Orders -- Chapter 25. Caddisflies: Insect Order Trichoptera -- Chapter 26. Beetles: Insect Order Coleoptera -- Chapter 27. Midges, Mosquitoes, Blackflies, and Other True Flies: Insect Order Diptera.
Includes bibliographical references (pages 263-266) and index.
Keywords: Freshwater invertebrates -- Ecology -- North America; Freshwater invertebrates -- Ecology -- North America -- Handbooks, manuals, etc; Freshwater invertebrates -- North America -- Identification; Freshwater invertebrates -- North America -- Identification -- Handbooks, manuals, etc; SCIENCE -- Life Sciences -- Zoology -- Invertebrates; Freshwater invertebrates; Freshwater invertebrates -- Ecology